THE PROTOTYPE OF GUIDANCE IN TRANSLATING MENU TEXT ASSET: A STUDY OF VIDEO GAME LOCALIZATION - Agung Prasetyo Wibowo (UIN Raden Mas Said Surakarta, 2021)
This study intends to create a guidance in translating video game text asset, mainly the menu in the game text asset. The research is done by identifying the game text asset, the techniques of translation applied, the quality of translation, the impacts caused by the usage of the techniques and its quality, and finally propose the recommended techniques to be used as guidance based on those aspects. In analyzing data, the researcher used a descriptive qualitative method using a case study of menu in a video game, namely Dragon Nest. The data were verified by experts in translation studies, linguistic, and video game. The sampling technique used was purposive sampling. Data collection techniques were carried out by document analysis, Foum Group Discussion (FGD), and questionnaire. Validation was done by data source triangulation and expert validation. Then the data analysis technique is using Spradley’s (1980) model of data analysis. The result of the study shows that the guidance in translating menu text asset of video game text should use these translation techniques (in order): Established Equivalence, adaptation, pure borrowing, and naturalized borrowing.